Trifluoromethylation of Arylsilanes with [(phen)CuCF3]. (23rd May 2016) - Morstein, Johannes; Hou, Haiyun; Cheng, Chen; Hartwig, John F.
Abstract: A method for the trifluoromethylation of arylsilanes is reported. The reaction proceeds with [(phen)CuCF3 ] as the CF3  source under mild, oxidative conditions with high functional‐group compatibility. This transformation complements prior trifluoromethylation of arenes in several ways. Most important, this method converts arylsilanes formed by the silylation of aryl C−H bonds to trifluoromethylarenes, thereby allowing the conversion of arenes to trifluoromethylarenes. The unique capabilities of the reported method are demonstrated by the conversion of a C−H bond into a C−CF3 bond in active pharmaceutical ingredients which do not undergo this overall transformation by alternative functionalization processes, including a combination of borylation and trifluoromethylation.